PENERAPAN TEKNOLOGI RFID DALAM IDENTIFIKASI BARANG BERBASIS INTERNET OF THINGS - Nurhalisah, Nurhalisah; Ahmad Rofiq Hakim; Wahyuni Eka Sari (CV. Denasya Smart Publisher, 2025)
The inventory recording process in the tool store of a mechanical engineering workshop is still done manually, making it prone to errors, delays, and difficulties in inventory management, especially when there are a large number of items or similar tools. This research aims to develop an RFID-based item identification system connected to the Internet of Things (IoT) to improve data collection efficiency and accuracy. The system uses an RFID RC522 to read the UID of the RFID card installed on each item, with a NodeMCU ESP8266 as the microcontroller. The UID and reading time are displayed on an I2C LCD and automatically sent to Google Sheets via an internet connection. Test results show the system is capable of reading and sending data with a success rate of up to 90%, while 10% of failures occur due to network connection disruptions. Thus, the system proves effective in automating the inventory recording process and minimizing human error.